New cost-effective pleural procedure training: manikin-based model to increase the confidence and competency in trainee medical officers. Issue 1123 (16th April 2019) - Heraganahally, Subash; Mehra, Sumit; Veitch, Daisy; Sajkov, Dimitar; Falhammar, Henrik; Morton, Sharon
Abstract: Purpose of the study: Pleural diseases are common in clinical practice. Doctors in training often encounter these patients and are expected to perform diagnostic and therapeutic pleural procedures with confidence and safely. However, pleural procedures can be associated with significant complications, especially when performed by less experienced. Structured training such as use of training manikin and procedural skills workshop may help trainee doctors to achieve competence. However, high costs involved in acquiring simulation technology or attending a workshop may be a hurdle. We hereby describe a training model using a simple manikin developed in our institution and provide an effective way to document skill acquisition and assessment among trainee medical officers. Study design: This was a prospective observational study. The need for training, competence and confidence of trainees in performing pleural procedures was assessed through an online survey. Trainees underwent structured simulation training through a simple manikin developed at our institute. Follow-up survey after the training was then performed to access confidence and competence in performing pleural procedures. Results: Forty-seven trainees responded to an online survey and 91% of those expressed that they would like further training in pleural procedure skills. 81% and 85% of responders, respectively, indicated preferred method of training is either practising on manikin or performing the procedure under supervision. Follow-up survey showed improvement in the confidence and competence. Conclusion: Our pleural procedure training manikin model is a reliable, novel and cost-effective method for acquiring competences in pleural procedures.